DNA Methylation Status in Cancer Disease: Modulations by Plant-Derived Natural Compounds and Dietary Interventions - Jasek, Karin; Kubatka, Peter; Samec, Marek; Liskova, Alena; Smejkal, Karel; Vybohova, Desanka; Bugos, Ondrej; Biskupska-Bodova, Kristina; Bielik, Tibor; Zubor, Pavol; Danko, Jan; Adamkov, Marian; et al. (Biomolecules, 2019)
The modulation of the activity of DNA methyltransferases (DNMTs) represents a crucial epigenetic mechanism affecting gene expressions or DNA repair mechanisms in the cells. Aberrant modifications in the function of DNMTs are a fundamental event and part of the pathogenesis of human cancer. Phytochemicals, which are biosynthesized in plants in the form of secondary metabolites, represent an important source of biomolecules with pleiotropic effects and thus provide a wide range of possible clinical applications. It is well documented that phytochemicals demonstrate significant anticancer properties, and in this regard, rapid development within preclinical research is encouraging. Phytochemicals affect several epigenetic molecular mechanisms, including DNA methylation patterns such as the hypermethylation of tumor-suppressor genes and the global hypomethylation of oncogenes, that are specific cellular signs of cancer development and progression. This review will focus on the latest achievements in using plant-derived compounds and plant-based diets targeting epigenetic regulators and modulators of gene transcription in preclinical and clinical research in order to generate novel anticancer drugs as sensitizers for conventional therapy or compounds suitable for the chemoprevention clinical setting in at-risk individuals. In conclusion, indisputable anticancer activities of dietary phytochemicals linked with proper regulation of DNA methylation status have been described. However, precisely designed and well-controlled clinical studies are needed to confirm their beneficial epigenetic effects after long-term consumption in humans.
Keywords: tumor suppressor genes; plant-based foods; cancer; Neoplasms; lidé; Humans; epigenetic modulations; phytochemicals; protinádorové látky; Antineoplastic Agents; metylace DNA; nádory; DNA Methylation; epigeneze genetická; Phytochemicals; Epigenesis, Genetic; oncogenes; DNA methylation patterns; fytonutrienty